If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4y = -18 Solving 5x + -4y = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 5x + -4y + 4y = -18 + 4y Combine like terms: -4y + 4y = 0 5x + 0 = -18 + 4y 5x = -18 + 4y Divide each side by '5'. x = -3.6 + 0.8y Simplifying x = -3.6 + 0.8y
| 3y-4=3y/5 | | 4.8=-14.6+x | | -6*5-(-13)= | | 4b-4-6b-6= | | -6*5-13= | | 10-x=173 | | 2*-1-y=1 | | 7(7+5f)+(f+6)10= | | 2*-7-y=1 | | a-45=55 | | f(x)=2f+6f | | 2*0-y=1 | | ln(x)+ln(3)=ln(4) | | 15x=-24 | | 2(x+1)/3=5x-3 | | x+y+z=20 | | 5a/4b^2-16b/25a^2 | | (4x^2-9)/(2x+3) | | -5(4y)-5+2(7y+8)= | | 2x^2/3-3x^1/3-20=0 | | 9d^2+24d+12=0 | | 4x(x-2)-3x(x+1)=-18 | | -11y=15-6t | | 7x^2y+4xy^2-7yx^2+5-6y^2x= | | y-24=37-20 | | 73-3x=7x+22 | | 2x^2/3-7x^1/3+6=0 | | x+6=3x-18 | | ln(x-6)+ln(5)=ln(30) | | 3nsquared=75 | | 5y+10x=15 | | 3(2x-7)-2(x-3)=-9 |